Kinetics of reactive extraction using waste catalyst for biodiesel production - Sulaiman, Sarina; Talha, Nur Syakirah; ..., Siti Noor Balqis (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
A kinetics study of in situ transesterification of solid coconut waste was conducted at temperature (55-65°C). The mixing is kept constant at 350 rpm. The maximum conversion of 38.3% was obtained at 60°C, 1:10 solid to methanol ratio and 5 wt. % of catalyst. The conversion of solid coconut waste to methyl esters was analyzed as functions temperature after 180 min of reaction. The experimental data appear to be a good fit into a pseudo first order kinetic model for the three stepwise reactions. The reaction rate constants, k and the activation energies, Ea were determined. In this study, the activation energy obtained from the experiment was 33.88 kJ/mol.